2020
DOI: 10.1002/lary.29169
|View full text |Cite
|
Sign up to set email alerts
|

Subglottic Stenosis Position Affects Work of Breathing

Abstract: Objectives: Subglottic stenosis (SGS) is the most common type of laryngeal stenosis in neonates. SGS severity is currently graded based on percent area of obstruction (%AO) via the Myer-Cotton grading scale. However, patients with similar %AO can have widely different clinical courses. Computational fluid dynamics (CFD) based on patient-specific imaging can quantify the relationship between airway geometry and flow dynamics. We investigated the effect of %AO and axial position of SGS on work of breathing (WOB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
(35 reference statements)
1
8
0
Order By: Relevance
“… 17 , 19 Computational fluid dynamic studies claim that anatomic variations such as the axial position of stenosis or the cross-sectional subglottic area may affect the perception of breathlessness. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 19 Computational fluid dynamic studies claim that anatomic variations such as the axial position of stenosis or the cross-sectional subglottic area may affect the perception of breathlessness. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…17,19 Computational fluid dynamic studies claim that anatomic variations such as the axial position of stenosis or the cross-sectional subglottic area may affect the perception of breathlessness. 30,31 The impact of subglottic stenosis in PFTs has been studied over the past few decades, although they are not routinely used in assessment and follow-up. Most of the test measurements improve postoperatively 14,15,19 ; yet, the EDI was found to be the most reliable parameter in diagnosing subglottic stenosis 12,13 and in monitoring treatment outcomes, [15][16][17][18][19] something supported by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…As the severity of subglottic narrowing increases, airway resistance and respiratory work increase exponentially. Clearly, the extent of the stenosis is the primary driver, but the length of the stenotic segment and the location of the stenosis in relationship with the glottis also impacts airway resistance 58‐60 . The narrowing and increased airway resistance most commonly manifests with biphasic stridor and increased respiratory effort.…”
Section: Fixed Airway Obstructionmentioning
confidence: 99%
“…According to Bernoulli's law, the faster the ow velocity, the lower the pressure generated by the uid, and the narrower the airway becomes as the tissue at the supraglottic site absorbs inward[16]. Yang et al suggested that air owing through the narrowing airway forms jets that create turbulent air ow, resulting in energy loss, which increases the respiratory work of the infant patient and can lead to failure to thrive [12].…”
Section: Discussionmentioning
confidence: 99%
“…CFD is often applied in the study of airway diseases, such as nasal diseases and obstructive sleep apnea hypoventilation syndrome [5,6], vocal cord dysfunction [4,7], and laryngotracheal stenosis [8]. Airway dynamics in infants and children have been less studied, and some studies have used unrealistic symmetric anatomical models to predict air ow dynamics [9,10], while a few reports have reconstructed realistic three-dimensional (3D) anatomical models of the airway from high-resolution computed tomography (CT) or magnetic resonance imaging (MRI) data for hydrodynamic studies of subglottic stenosis and tracheomalacia in pediatric patients [11][12][13]. However, no studies have been conducted on the airway in children with LM based on the hydrodynamics of CT reconstructed 3D models.…”
Section: Introductionmentioning
confidence: 99%